Forest Restoration in Landscapes Beyond Planting Trees - Mansourian, Stephanie; Vallauri, Daniel (Springer New York : Imprint: Springer, 2005)
The importance of restoration continues to grow, and this book integrates the restoration of forest functions into landscape conservation plans. The global conservation organization WWF has made forest landscape restoration a key topic and priority for its environmental work. Due to the WWF's extensive global reach, and together with its many partners and counterparts, it has acquired a significant level of experience on the topic of forest restoration at large scales. This book represents the collective body of knowledge and experience of WWF and its many partners--which is collected here for the first time and which will be invaluable to all of those working in the field. This guide will serve as a first stop for practitioners and researchers in any organization or region and as a key reference on the subject. Along with concise, practical information for a variety of specific systems and issues, it gives many suggestions for further research. From the Foreword by Chief Anyaoku, President, WWF International: "Is it a sign of the times that the Nobel committee chose to award the Nobel Peace prize to Wangari Maathai for having planted 30 million trees? We believe so. . . .The 21st Century will be a time of forest restoration.".